Prevalence of constipation and associated factors among undergraduate students of Faculty of Allied Health Sciences, University of Jaffna. - Abeygunasekara, L.R.; Mihirani, A.; Jegapragash, V.; Kajendran, A. (University of Jaffna, 2023)
Introduction: Constipation is a common chronic gastrointestinal complaint and, although not life-threatening, is physically and mentally inconvenient condition for many patients. The health-related quality of life is diminished in the group of constipated population. And also, chronic constipation has major impact on life. Impact of the constipation should not be underestimated and it can result in high expenditure for the health care cost as well as burden on the health care system. Objective: To assess the prevalence of constipation and associated factors among undergraduate students, Faculty of Allied Health Sciences, University of Jaffna. Methodology: This was an institutional based descriptive cross-sectional study carried out among 426 undergraduate students, Faculty of Allied Health Sciences, University of Jaffna. Data were collected by using pretested self-administered questionnaire. The descriptive statistics was used to describe the variables and chi square test was performed to identify association among variables. Ethical clearance was obtained to carry out this study. Results: There were 426 undergraduate students recruited as sample for this study and 90.14% were responded. Mean age of the participants were 24.2 (SD= 0.478) and 65.6% were female. According to the academic year, participants were almost evenly distributed. Among the participants, prevalence of functional constipation and self-reported constipation were 25.5% and 33.3% respectively. Gender, intake of self-medication, fibre food intake, fast food consumption and consumption of water were significantly associated with the self-reported constipation while intake of self-medication, fibre food intake and consumption of beverages were significantly associated with functional constipation. Conclusion: The prevalence of self-reported constipation and functional constipation were significantly prevailed among the population. Prevalence of self- reported constipation was more common in females than male.
Keywords: Constipation; Prevalence; Associated factors; Undergraduate